Endoscopic dilation in pediatric esophageal strictures: a literature review - Ghiselli, Alessia; Bizzarri, Barbara; Ferrari, Daniela; Manzali, Elisabetta; Gaiani, Federica; Fornaroli, Fabiola; Nouvenne, Antonio; Di Mario, Francesco; de'Angelis, Gian Luigi (Acta Biomedica Atenei Parmensis, 2018)
Background: Esophageal strictures in pediatric age are a quite common condition due to different etiologies. Esophageal strictures can be divided in congenital, acquired and functional. Clinical manifestations are similar and when symptoms arise, endoscopic dilation is the treatment of choice. Our aim was to consider the efficacy of this technique in pediatric population, through a wide review of the literature. Method: A search on PubMed/Medline was performed using “esophageal strictures”, “endoscopic dilations” and “children” as key words. Medline, Scopus, PubMed publisher and Google Scholar were searched as well. As inclusion criteria, we selected clinical studies describing dilations applied to all type of esophageal strictures in children. Papers referred to single etiology strictures dilations or to adult population only were excluded, as well as literature-review articles. Results: We found 17 studies from 1989 to 2018. Overall, 738 patients in pediatric age underwent dilation for esophageal strictures with fixed diameter push-type dilators (bougie dilators) and/or radial expanding balloon dilators. Severe complications were observed in 33/738 patients (4,5%) and perforation was the most frequent (29/33). Conversion to surgery occurred only in 16 patients (2,2%). Conclusions: Endoscopic dilation is the first-choice treatment of esophageal strictures, it can be considered a safe procedure in pediatric age. Both, fixed diameter push-type dilators and radial expanding balloon dilators, showed positive outcomes in term of clinical results and cases converted to surgery. However, it’s essential to perform these procedure in specialized Centers by an experienced team, in order to reduce complications.